2019
DOI: 10.1002/cncr.32188
|View full text |Cite
|
Sign up to set email alerts
|

Association between advanced cancer patient‐caregiver agreement regarding prognosis and hospice enrollment

Abstract: BACKGROUND: Patients with advanced, incurable cancer who understand their illness is incurable are more likely to prefer hospice care at the end of life compared with patients who believe their illness is curable. To the authors' knowledge, it is unclear whether patient-caregiver agreement regarding perceived prognosis is associated with hospice enrollment. METHODS: The current study examined the prospective relationship between patient-caregiver agreement concerning perceived prognosis and hospice enrollment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 50 publications
2
24
0
Order By: Relevance
“…
We appreciate the letter from Kako et al regarding our examination of the relationship between advanced cancer patient-caregiver agreement regarding perceived prognosis and hospice enrollment within the last 30 days of life. 1 In general, we agree with Kako et al and welcome this opportunity to expand our discussion of this important topic.Kako et al raised questions concerning how and when prognostic information should be provided that are critical to the translation of research into clinical care. A highly structured formulaic approach to prognostic discussions is unlikely to be effective when working with individual patients who vary with regard to disease status, emotional readiness for prognostic information, and caregiver support, among other factors.
…”
supporting
confidence: 84%
See 2 more Smart Citations
“…
We appreciate the letter from Kako et al regarding our examination of the relationship between advanced cancer patient-caregiver agreement regarding perceived prognosis and hospice enrollment within the last 30 days of life. 1 In general, we agree with Kako et al and welcome this opportunity to expand our discussion of this important topic.Kako et al raised questions concerning how and when prognostic information should be provided that are critical to the translation of research into clinical care. A highly structured formulaic approach to prognostic discussions is unlikely to be effective when working with individual patients who vary with regard to disease status, emotional readiness for prognostic information, and caregiver support, among other factors.
…”
supporting
confidence: 84%
“…We appreciate the letter from Kako et al regarding our examination of the relationship between advanced cancer patient-caregiver agreement regarding perceived prognosis and hospice enrollment within the last 30 days of life. 1 In general, we agree with Kako et al and welcome this opportunity to expand our discussion of this important topic.…”
supporting
confidence: 84%
See 1 more Smart Citation
“…1,2 Several studies have demonstrated that prognostic understanding affects health care use and advanced care planning. [3][4][5][6][7] Therefore, there is a need to improve prognostic understanding so that patients receive care concordant with their goals. Caregivers (generally family members or friends) play an integral role in the care of older adults, 8 and many participate in prognostic discussions and assist patients with treatment decision making.…”
Section: Introductionmentioning
confidence: 99%
“…We read with great interest the recent article by Trevino et al 1 The authors concluded that the rates of hospice enrollment differed according to patient-caregiver agreement regarding the patient's prognosis and perception of future quality of life. These results are very interesting, but we would like to highlight 3 concerns.…”
mentioning
confidence: 99%